Instructional strategies for the differentiated classroom : intelligence preferences. - ASCD (Alexandria, Va : Association for Supervision and Curriculum Development, 2003)
Library has
Facilitator's guide, Tapes 1,2,3,4.
Keywords: Curriculum planning (Instructional strategies) -- United States; Effective teaching -- United States; Academic achievement -- United States; Research-based instructional strategies -- United States